2020
DOI: 10.1080/02656736.2020.1778800
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released by breast cancer cells under mild hyperthermic stress possess immunogenic potential and modulate polarization in vitro in macrophages

Abstract: Macrophages play a dual role in tumor initiation and progression, with both tumor-promoting and tumor-suppressive effects; hence, it is essential to understand the distinct responses of macrophages to tumor progression and therapy. Mild hyperthermia has gained importance as a therapeutic regimen against cancer due to its immunogenic nature, efficacy, and potential synergy with other therapies, yet the response of macrophages to molecular signals from hyperthermic cancer cells has not yet been clearly defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…The transcription of IL-1β, COX-2, IL-12p40, SOCS3, MSR1 andMRC1 was analyzed by qPCR, as we described previously [ 57 ]. The transcription of murine iNOS and Arg-1 were analyzed by using the primers described previously [ 60 ], while transcripts of TNF, IL-10 were performed utilizing the following primer sequences: TNF-Forward:CCTGTAGCCCACGTCGTAGC; TNF-Reverse:AGCAATGACTCCAAAGTAGACC; IL-10 Forward: TGCACTACCAAAGCCACAAAGCAG; IL-10 Reverse:TCAGTAAGAGCAGGCAGCATAGCA. Briefly, RNA was extracted from cells using a Qiagen RNeasy Mini Plus extraction kit.…”
Section: Methodsmentioning
confidence: 99%
“…The transcription of IL-1β, COX-2, IL-12p40, SOCS3, MSR1 andMRC1 was analyzed by qPCR, as we described previously [ 57 ]. The transcription of murine iNOS and Arg-1 were analyzed by using the primers described previously [ 60 ], while transcripts of TNF, IL-10 were performed utilizing the following primer sequences: TNF-Forward:CCTGTAGCCCACGTCGTAGC; TNF-Reverse:AGCAATGACTCCAAAGTAGACC; IL-10 Forward: TGCACTACCAAAGCCACAAAGCAG; IL-10 Reverse:TCAGTAAGAGCAGGCAGCATAGCA. Briefly, RNA was extracted from cells using a Qiagen RNeasy Mini Plus extraction kit.…”
Section: Methodsmentioning
confidence: 99%
“…Although no preclinical and clinical evidence suggests that local HT has the ability to induce a systemic antitumor response, recent studies have demonstrated that antitumor immunity is stimulated by local HT via HSP induction [10,12,29]. A recent study reported that exosomes released from breast cancer cells treated with HT possessed an immunogenic potential [30]. Together with the strong enhancement of T cell activity and Treg blocking function by C4 [17], we hypothesized that local HT in combination with C4 could enhance systemic antitumor efficacy and alter immune cell microenvironments not only in local tumors but also in distant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in temperature have been shown to impact the efflux quantity of EVs by tumor cells. One study found that high temperatures in tumor hyperthermia significantly enhance the release of tumor cell EVs [94]. However, this hyperthermia method also caused the volume of each individual EV to increase.…”
Section: Increasing Ev Productionmentioning
confidence: 99%